(untitled) (Research, Society and Development, 2020)
This study aimed to identify the level of knowledge, attitudes and practices related to biosafety measures, prevention and control by dental surgeons (DCs) during the pandemic. An online questionnaire consisting of 42 questions was disseminated to the DCs operating in Brazil through social networks and also to the 27 Regional Councils of Dentistry in the country via e-mail. The collection period was from June 26 to July 2, 2020. A total of 751 DCs answered the questionnaire, of these, 54.9% undertook training in preventing and controlling the spread of the virus and the scientific article was the main means of information (44.5%). Regarding biosafety in dental care, 95.9% reported having knowledge of ANVISA’s rules on the subject, however, regarding attitudes and practices, there was a failure to comply with the recommendations. Link between professional performance and training or not, were factors associated with greater knowledge and correct biosafety attitudes and practices. Although the Brazilian DCs have good levels of knowledge about biosafety measures for the prevention of COVID-19, they still fail to comply with basic attitudes and recommended practices.